Test driven development in Microsoft.Net - Newkirk, James (Microsoft Press, 2004)
Apply the concepts and techniques of Test-Driven Development to building Microsoft .NET-connected applications. Two experts in agile software development demonstrate by example how to use tests to drive lean, efficient coding and better design.